Upaya Meningkatkan Hasil Belajar IPA Siswa Melalui Model Pembelajaran Round Club - Nurhadi, Nurhadi (JURNAL GLOBAL EDUKASI, 2017)
Abstract: The purpose of this class action research is to find out the improvement of science learning outcomes of students on the subject matter of the earth and the universe through the Round Club learning model. Subjects in this study were students of class VI SD Negeri 018439 Sentang district Kisaran Timur of the academic year 2016/2017 totaled 37 students. The results obtained that the learning outcomes in the first cycle reached an average value of 78.62 after cycle I and cycle II, reflection and recommendation average value reached 83.89. In the first cycle, the percentage of learning completeness classical obtained by 78.64%, after improving the learning in cycle II the percentage of learning completeness classical to 88.41%. It can be concluded that the application of Round Club learning model can improve student learning outcomes of grade VI SD Negeri 018439 Sentang district Kisaran Timur of the academic 2016/2017 on the subject matter of the earth and the universe. Keywords: Round Club, earth, universe Abstrak: Tujuan penelitian tindak kelas ini adalah untuk mengetahui peningkatkan hasil belajar IPA siswa pada materi pokok bumi dan alam semesta melalui model pembelajaran Round Club. Subjek dalam penelitian ini adalah siswa kelas VI SDN 018439 Sentang kec. Kisaran Timur tahun pelajaran 2016/2017 berjumlah 37 siswa. Hasil penelitian diperoleh bahwa hasil belajar pada siklus I mencapai nilai rata-rata 78,62 setelah siklus I dan siklus II, refleksi dan rekomendasi nilai rata-rata mencapai 83,89. Pada siklus I persentase ketuntasan belajar klasikal diperoleh sebesar 78,64%, setelah dilakukan perbaikan pembelajaran pada siklus II persentase ketuntasan belajar klasikal meningkat menjadi 88,41%. Dapat disimpulkan bahwa penerapan model pembelajaran Round Club dapat meningkatkan hasil belajar siswa kelas VI SDN 018439 Sentang kec. Kisaran Timur tahun pelajaran 2016/2017 pada materi pokok bumi dan alam semesta. Kata kunci: Round Club, bumi, alam semesta